Time in the Work of Frank Lloyd Wright - Frans Sturkenboom (A+BE: Architecture and the Built Environment)
For a long time Wright’s architecture has been theorized in terms of space. Although space was certainly a key-word in Wright’s discourse, we can neither see it as an objective, three-dimensional space, nor as a more subjective, intimate space. In Wright’s architecture, the third dimension implies time, an axis mundi, a story about the earth as being built. Architecture faces the task to explicate this geological dimension. Geology here not only pertains to the crust of the earth and its materials. It also refers to flora and fauna, all the life having co-built the earth. Designing means the digging up of this natural history of a place that should come to resonate in structure, texture, type, pattern, colour and form. Architecture finds its reason in this geological time, it memorizes that time. Every Wright House is a monument of the American landscape. A new space appears: no longer Cartesian threedimensional space, not human-centred place-space, but the shallow space of the building as a bas-relief of the earth, “growing out of the ground into the light.”